An International Interprofessional Study of Mental Models and Factors Delaying Neuroimaging of Critically Head-Injured Children Presenting to Emergency Departments. Issue 11 (November 2018) - Auerbach, Marc; Cole, Joanne; Violano, Pina; Roney, Linda; Doherty, Catherine; Shepherd, Michael; MacKinnon, Ralph
Abstract : Objectives: Thousands of head-injured children are cared for by interprofessional teams in emergency departments every day. Teams must balance performing time-consuming interventions with safe transport for neuroimaging. This study aims to describe and compare providers' perspectives on the transfer of head-injured children to neuroimaging and factors contributing to delays. Methods: Participants were interprofessional health care providers involved in the care of head-injured children at sites in the United Kingdom, the United States, and New Zealand. They first viewed a 3-minute video of a child with a severe head injury presenting to their resuscitation bay. Next, they were presented with 5 physiologically different simulated scenarios and asked to report whether interventions were required before transporting each patient to neuroimaging. Then, they reported team and system factors contributing to delays in neuroimaging. Results: Two hundred forty of 296 providers completed the intervention. The percentage of providers reporting that they would directly transport to neuroimaging without intervention was 89% for "stable, " 49% for "Cushing's triad, " 26% for "hypoxic, " 25% for "tachycardic, " and 5% for "extremis." There were differences noted in responses by profession for the hypoxia and tachycardia cases. No differences were noted between trainees and attending physicians for any cases. The most frequent factors reported as delaying neuroimaging were team decision making and waiting for equipment, medications, and scanner availability. Conclusions: There is variability in providers' perspectives on the interventions required before transporting severely head-injured patients for imaging. Diverse team and system factors contribute to delays in imaging. Abstract : Supplemental digital content is available in the text.